Consolidation immunotherapy after platinum-based chemoradiotherapy in patients with unresectable stage III non-small cell lung cancer: cross-sectional study of eligibility and administration rates - Eichkorn, Tanja; Bozorgmehr, Farastuk; Regnery, Sebastian; Dinges, Lisa A.; Kudak, Andreas; Bougatf, Nina; Kronsteiner, Dorothea; Christopoulos, Petros; Muley, Thomas; Kobinger, Sonja; König, Laila; Hörner-Rieber, Juliane; et al. (Frontiers in oncology, 2020)
Introduction: The PACIFC trial demonstrated a significant benefit of durvalumab consolidation immunotherapy (CIT) after definitive platinum-based chemoradiotherapy (P-CRT) for survival in stage III non-small cell lung cancer (NSCLC). It is unknown how many patients are eligible in clinical practice to receive CIT according to PACIFIC criteria compared to real administration rates and what influencing factors are. Patients and methods: We analyzed 442 patients with unresectable stage III NSCLC who received P-CRT between 2009 and 2019 regarding CIT eligibility rates according to PACIFIC criteria and administration rates since drug approval. Results: 64% of 437 patients were male, median age was 63 years (interquartile range (IQR): 57 - 69). The most common histologic subtypes were adenocarcinoma (42.8%) and squamous cell carcinoma (41.1%), most tumors were in stage IIIB (56.8%). Mean PD-L1 tumor proportion score (TPS) was 29.8% (IQR: 1 - 60). The median total RT dose was 60 Gy (IQR: 60 - 66). Platinum component of P-CRT was evenly distributed between cisplatin (51.4%) and carboplatin (48.6%). 50.3% of patients were eligible for CIT according to PACIFIC criteria. Observed contraindications were progressive disease according to RECIST (32.4%), followed by a PD-L1 TPS <1% (22.3%), pneumonitis CTCAE ≥°2 (12.6%) and others (4.9%). One year after drug approval, 85.6% of patients who were eligible according to PACIFIC criteria actually received CIT. Time interval between chemotherapy start and radiation therapy start (OR 0.9, 95%-CI: [0.9;1.0] p=0.009) and probably cisplatin as platinum-component of P-CRT (OR 1.5, 95%-CI: [1.0;2.4] p<0.061) influence CIT eligibility. Highly positive PD-L1 TPS (≥50%; (OR 2.4, 95%-CI: [1.3;4.5] p=0.004) was associated to a better chance for CIT eligibility. Conclusion: 85% of potentially eligible patients received CIT one year after drug approval. 50% of patients did not meet PACIFIC criteria for durvalumab eligibility, this was mainly caused by disease progression during platinum-based CRT, followed by therapy-related pneumonitis and PD-L1 TPS <1% (in view of the EMA drug approval).
Gesehen am 15.12.2020